Beliefs of Adolescents on Sugar-Sweetened Beverages Abstinence: A Reasoned Action Approach Elicitation Study - Beaulieu, Dominique; Vézina-Im, Lydi-Anne; Simard, Dominic; Boucher, Danielle (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2018)
Introduction. Sugar-sweetened beverage (SSB) consumption is associated with many health problems, such as obesity and cardiovascular diseases. Objectives. To identify adolescents’ beliefs concerning SSB abstinence. Methods. Based on the Reasoned Action Approach, thirty semi-structured interviews were conducted with adolescents (12-17 years). They were selected based on age, sex and setting in order to ensure a broad representation of adolescents from two French-speaking regions of the province of Quebec in Canada (Eastern Canada). Adolescents were invited to answer eight open-ended questions regarding SSB abstinence in the next month. A qualitative content analysis was performed independently by two experts to identify the most important beliefs. Results. According to adolescents, the main advantage of abstaining from SSB was that it would be good for their health and the main disadvantage was that they would have to give up products they liked drinking for the taste. Parents and friends seemed to be the most important social influences regarding abstaining from SSB. Adolescents mentioned many barriers to SSB abstinence, such as contextual barriers (e.g., special occasions, eating out, following sports activities), the presence of SSB drinkers, advertisements promoting SSB, and the urge to drink SSB. Facilitating factors included absence of SSB at home/school, having easy access to water and pure fruit juices, and receiving information about the negative health effects of SSB. Discussion/Conclusions. The results of this preliminary study can be used to guide the development of interventions to promote SSB abstinence among adolescents.